Patient, psychiatrist and family carer experiences of community treatment orders: qualitative study. - Canvin, K; Rugkåsa, J; Sinclair, J; Burns, T (2014)
PURPOSE: Current literature on personal experiences of community treatment orders (CTO) is limited. This paper examines participants' experiences of the mechanisms via which the CTO was designed to work: the conditions that form part of the order and the power of recall. We also report an emergent dimension, legal clout and participants' impressions of CTO effectiveness. This paper will contribute to a fuller picture of how the law is implemented and how CTOs operate in practice. METHODS: In-depth qualitative interviews were conducted with a purposive sample of 26 patients, 25 psychiatrists and 24 family carers about their experiences and views of CTOs. Data were analysed using the constant comparative method. RESULTS: All three sample groups perceived the chief purpose of CTOs to be medication enforcement and that its legal clout was central to achieving medication adherence. Understanding of how the inbuilt mechanisms of the CTO work varied considerably: participants expressed uncertainty regarding the enforceability of discretionary conditions and the criteria for recall. We found mixed evidence regarding whether recall simplified responses to relapse or risk. The range of experiences and views identified within each group suggests that there is no single definitive experience or view of CTOs. CONCLUSIONS: The (perceived) focus of the CTO on medication adherence combined with the variations in understanding within and across groups might not only have consequences for how CTOs are viewed and subsequently experienced, but also for broader goals in patient care and patient and carer involvement.